MGMT promoter methylation is a strong prognostic biomarker for benefit from dose-intensified temozolomide rechallenge in progressive Glioblastoma: The DIRECTOR Trial - Weller, Michael; Tabatabai, Ghazaleh; Kästner, Bärbel; Felsberg, Jörg; Steinbach, Joachim P.; Wick, Antje; Schnell, Oliver; Hau, Peter; Herrlinger, Ulrich; Sabel, Michael C.; Wirsching, Hans Georg; Ketter, Ralf; et al. (Clinical Cancer Research, 2015)
Purpose: Rechallenge with temozolomide (TMZ) at first progression of glioblastoma after temozolomide chemoradiotherapy (TMZ/RT!TMZ) has been studied in retrospective and single-Arm prospective studies, applying temozolomide continuously or using 7/14 or 21/28 days schedules. The DIRECTOR trial sought to show superiority of the 7/14 regimen. Experimental Design: Patients with glioblastoma at first progression after TMZ/RT!TMZ and at least two maintenance temozolomide cycles were randomized to Arm A [one week on (120 mg/m2 per day)/one week off] or Arm B [3 weeks on (80 mg/m2 per day)/one week off]. The primary endpoint was median timeto-treatment failure (TTF) defined as progression, premature temozolomide discontinuation for toxicity, or death from any cause. O6-methylguanine DNA methyltransferase (MGMT) promoter methylation was prospectively assessed by methylationspecific PCR. Results: Because of withdrawal of support, the trial was prematurely closed to accrual after 105 patients. There was a similar outcome in both arms for median TTF [A: 1.8 months; 95% confidence intervals (CI), 1.8-3.2 vs. B: 2.0 months; 95% CI, 1.8-3.5] and overall survival [A: 9.8 months (95% CI, 6.7-13.0) vs. B: 10.6 months (95% CI, 8.1-11.6)]. Median TTF in patients with MGMT-methylated tumors was 3.2 months (95% CI, 1.8- 7.4) versus 1.8 months (95% CI, 1.8-2) in MGMT-unmethylated glioblastoma. Progression-free survival rates at 6 months (PFS-6) were 39.7% with versus 6.9% without MGMT promoter methylation. Conclusions: Temozolomide rechallenge is a treatment option for MGMT promoter-methylated recurrent glioblastoma. Alternative strategies need to be considered for patients with progressive glioblastoma without MGMT promoter methylation.
CRIS-Team Scopus Importer:2023-09-13